Genetic variation of Gmelina arborea Roxb in Trenggalek, East Java. Issue 1 (November 2021) - Setiadi, D; Susanto, M; Baskorowati, L; Mashudi,; Pudjiono, S
Abstract: White teak ( Gmelina arborea Roxb) is an introduced species of the verbenaceae. This study observed genetic variation of G. arborea in Trenggalek, East Java. Incomplete Block Design was used for this trial comprising four replications, five populations, 50 families, and three tree plots with planting space of 3 x 2 m. Significant differences between seed origins for height and survival rate were exhibited in this study; however, no significant differences between populations for diameter traits at 1 st year old. Meanwhile, significant differences between populations for height, diameter, and survival rate existed at second years old. The mean survival rate at first and second years old were 98, 44% and 95, 95%, height were 1.23 m and 2.86 m, and stem diameter was 2.18 cm and 3.66 cm. Moderate heritability's showed for height and diameter were (h 2 i = 0.29; h 2 f = 0.30), (h 2 i = 0.24; h 2 f = 0, 38) and (h 2 i = 0.19; h 2 f = 0.30), (h 2 i = 0.18; h 2 f = 0.28). Genetic correlation for height and diameter were rg = 0.75, and rg = 0.89. Genetic variation growth of G. arborea progeny test can be used as basic information of the plus trees selection with good performance. Therefore, the open pollination between remaining plus tress will produce a good quality of seed, which will increase the volume of timber harvested.